Human Induced Pluripotent Stem Cell-Derived Brain Endothelial Cells: Current Controversies - Lu, Tyler M.; Barcia Durán, José Gabriel; Houghton, Sean; Rafii, Shahin; Redmond, David; Lis, Raphaël (Frontiers in Physiology, 2021)
Brain microvascular endothelial cells (BMECs) possess unique properties that are crucial for many functions of the blood-brain-barrier (BBB) including maintenance of brain homeostasis and regulation of interactions between the brain and immune system. The generation of a pure population of putative brain microvascular endothelial cells from human pluripotent stem cell sources (iBMECs) has been described to meet the need for reliable and reproducible brain endothelial cells in vitro. Human pluripotent stem cells (hPSCs), embryonic or induced, can be differentiated into large quantities of specialized cells in order to study development and model disease. These hPSC-derived iBMECs display endothelial-like properties, such as tube formation and low-density lipoprotein uptake, high transendothelial electrical resistance (TEER), and barrier-like efflux transporter activities. Over time, the de novo generation of an organotypic endothelial cell from hPSCs has aroused controversies. This opinion article highlights the developments made in the field of hPSC derived brain endothelial cells as well as where experimental data are lacking, and what concerns have emerged since their initial description.